To study the practical problems of attention and memory processes in children with speech defects (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the practical study of attention and memory processes in children with speech defects, phonetic and phonemic disorders of speech, bilingualism - bilingualism, disorders of pronunciation of sounds, and provides psychological recommendations